Safety and Effectiveness of Juvéderm Ultra Plus Injectable Gel in Correcting Severe Nasolabial Folds in Chinese Subjects. Issue 1 (January 2017) - Li, Dong; Xie, Yun; Li, Qin; Sun, Jiaming; Jiang, Ping; Jia, Yi; Murphy, Diane K.; Li, Qingfeng
Abstract : Background: Hyaluronic acid dermal fillers are effective in correcting severe nasolabial folds (NLFs) in non-Asian populations. We assessed safety and effectiveness of Juvéderm Ultra Plus in a Chinese population. Methods: This double-blind study randomized Chinese subjects with severe NLFs to Juvéderm Ultra Plus (24 mg/mL) in 1 NLF and Restylane injectable gel (20 mg/mL) in the other NLF. NLFs were evaluated using the validated 5-point photonumeric Allergan NLF Severity Scale (0 is "no wrinkle" and 4 is "very deep wrinkle"). Investigator-assessed responder rates (primary outcome at 6 months), NLF mean improvements, and subject-assessed responder rates and preference were assessed. Results: Of 124 subjects randomized, 122 completed the 6-month visit. NLFs treated with Juvéderm Ultra Plus required less volume than those treated with Restylane (median [range]: 0.80 [0.3–2.0] vs 1.00 [0.3–1.9]; P <0.001). Investigator-assessed responder rates were 90.4% for Juvéderm Ultra Plus and 89.6% for Restylane, establishing noninferiority of Juvéderm Ultra Plus. Mean (SD) improvements in NLF Severity Scale scores from baseline at 6 months were 1.5 (0.75) for Juvéderm Ultra Plus and 1.6 (0.73) for Restylane. Subject-assessed responder rates were similar to investigator-assessed rates (87.3%, Juvéderm Ultra Plus; 83.9%, Restylane). Of subjects reporting a preference, 62.1% preferred Juvéderm Ultra Plus. The most common treatment site responses were swelling and tenderness; most were mild or moderate in severity and resolved without intervention. Juvéderm Ultra Plus had fewer severe treatment site responses than Restylane. Conclusion: In this study in Chinese subjects, Juvéderm Ultra Plus was safe and effective for correcting severe NLFs.